On the Fitting ideals of a multiplication module - Hadjirezaei, S.; Karimzadeh, S. (Algebra and Discrete Mathematics, 2018)
In this paper, we characterize all finitely generated multiplication R-modules whose the first nonzero Fitting ideal of them is contained in only finitely many maximal ideals. Also, we prove that a finitely generated multiplication R-module M is faithful if and only if M is a projective of constant rank one R-module.